Oceanography and Marine Biology An Annual Review, Volume 59 - Hawkins, S.J; Lemasson, A. J.; Allcock, A.L; Bates, A. E.; Byrne, M.; Evans, A J.; Firth, L.B; Marzinelli, E.M; Russell, B.D; Smith, I.P; Swearer, S.E; Todd, P.A (Oceanography and Marine Biology - An Annual Review, 2022)
CHOICE Highly Recommended, Sept 2022 Oceanography and Marine Biology: An Annual Review remains one of the most cited sources in marine science and oceanography. The ever-increasing interest in work in oceanography and marine biology and its relevance to global environmental issues, especially global climate change and its impacts, creates a demand for authoritative refereed reviews summarizing and synthesizing the results of recent research. For nearly 60 years, OMBAR has been an essential reference for research workers and students in all fields of marine science. This volume considers such diverse topics as the Great Barrier Reef Expedition of 1928-29, Mediterranean marine caves, macromedusae in eastern boundary currents, marine biodiversity in Korea, and development of a geo-ecological carbonate reef system model to predict responses of reefs to climate change. Volume 59 is available to read Open Access on the Taylor & Francis eBooks site (https://www.taylorfrancis.com/books//10.1201/9781003138846) An international Editorial Board ensures global relevance and expert peer review, with editors from Australia, Canada, Hong Kong, Ireland, Singapore and the United Kingdom. The series volumes find a place in the libraries of not only marine laboratories and oceanographic institutes, but also universities worldwide. If you are interested in submitting a review for consideration for publication in OMBAR, please email the Editor in Chief, Stephen Hawkins, at S.J.Hawkins@soton.ac.uk.